Immunohistochemical Expression of Alpha Smooth Muscle Actin Positive Myofibroblast and Laminin 5 gamma 2 in Squamous Cell Carcinoma and Verrucous Carcinoma of the Oral Cavity - Homeyra Mardani; Bahareh Rashnavadi; Noshin Afshar Moghadam (Isfahan University of Medical Sciences, 2022)
Squamous cell carcinoma is the most common type of oral cancer that shows certain tissue changes. Laminin-5γ2 is a protein that plays a central role in migration of the neoplastic cells during tumor invasion. Expression of this protein in cells and stroma adjacent to tumor can confirm the cellular invasion. The aim of this study was to evaluate stroma in verrucous carcinoma and squamous cell carcinoma of the mouth using two markers α SMA and laminin 5 gamma 2.Materials & Methods:In this retrospective descriptive-analytical study, 60 samples were selected with the diagnosis of squamous cell carcinoma and verrucous oral carcinoma. Then, two markers of α SMA and laminin 5 gamma 2 were examined in epithelium and mesenchymal stroma by immunohistochemistry. The vasculature was used as a positive immunoreactivity control for alpha-smooth muscle and the normal mucosa was used to control the positive immunoreactivity of laminin 5 gamma 2. The results were analyzed using Chi-square and Spearman correlation tests (α = 0.05).Results:Out of 31 SCC samples, 80.6% showed laminin 5 gamma 2 and 90.3% showed alpha smooth and out of 9 samples of varocus carcinoma, 66.7% showed laminin 5 gamma 2 and 77.8% showed alpha smooth actin.The higher the positive percentage of laminin, the higher the percentage of positive α SMA.Conclusion:Expression of alpha smooth muscle actin and lamminin5gamma2 was significantly higher in oral squamous cell carcinoma and there exists a correlation between expression of alpha smooth muscle actin and the increase in myofibroblaststakes place during the carcinogenesis process